Social Networks Apps and their Role in Tourism Marketing in the Kingdom of Saudi Arabia - Al-Hazmi, Nabil Mohemmed (International Journal of Interactive Mobile Technologies (iJIM), 2021)
This study aimed at investigating the role of social networks apps in tourism marketing for travel and tourism organizations in Al-Kharj City, Kingdom of Saudi Arabia. The study used the descriptive and analytical approach to achieve its objectives and test its hypothesis. The study found that social networks apps play a vital role in marketing the tourism product in Al-Kharj City as well as communicating effectively and cheaply with the customers. The study recommended nominating and training some workers in tourism organizations to deal with social media networks and design websites and applications for these organizations.